Pengaruh Kompetensi Terhadap Produktivitas Kerja Karyawan Dengan Motivasi Sebagai Variabel Moderator Di PT PLN (Persero) Pusat Pemeliharaan Ketenaga Listrika Unit Workshop Dan Pemeliharaan IV (Pusharlis UWP IV) Kota Pagaralam - Marko Ilpiyanto (Jurnal Manajemen dan Bisnis, 2020)
Work productivity will increase if employees have good work competencies. However, sufficient work competence to produce high work productivity requires the existence of other driving factors. One of the factors driving work competence that can affect work productivity is work motivation. This study aims to determine the effect of competence on work motivation with motivation as a moderate variable in PT PLN (Persero) Electricity Maintenance Center Workshop and Maintenance Unit IV (PUSHARLIS UWP IV). The method used in this research is quantitative method with descriptive research type. Respondents in this study were employees with a population of 45 respondents. Sampling with saturated sampling technique. The results showed that work competence, motivation and work productivity were in the high category. The results of the study have a significant effect on work productivity. The results also show that motivation is a variable that affects the positive relationship between work competence and work productivity. This means that increasing motivation will also increase employee productivity.